Tinjauan Hukum Agraria terhadap Privatisasi Sempadan Pantai oleh Korporasi - Diah Rahmawati; Nurzamzawiah Kudus; Ni Luh Niken Ayu Tresta; Michel Aurelia Safira (CV Rewang Rencang, 2025)
Coastal borders play a strategic role for coastal ecosystems and communities but are often privatized by corporations for resort development. This practice alters ecological functions and creates agrarian conflicts between corporations, government, and society. This study analyzes the Bali Provincial Government’s policies regarding coastal border privatization within the framework of agrarian law, using a normative method with statute and conceptual approaches. Findings reveal the absence of specific regulations and weak supervision, highlighting the need for strengthened regulatory policies to safeguard public interests and ensure environmental sustainability.